واقع الحرية في الحضارات القديمة ومنطلقات ممارستها في المجتمعات الإسلامية المعاصرة (The Reality of Freedom in Past Civilizations and Its Practices in Contemporary Islamic Societies) - Murshed, Amer Abdulwahab Mahyoub; Amer, Eftekhar Ali Abdo (Journal of Al-Tamaddun, 2021)
Historical reading of the actual picture of freedom in ancient civilizations and today’s realities indicates that the values of freedom and human rights have been violated. It also indicates that people have been subjugated by authoritarian regimes. The purpose of this research is to reflect on the actual reality of freedom in contemporary Islamic societies. To this effect, the study adopted a descriptive and historical approach using a survey to review the opinions of academics about freedom in contemporary Islamic societies. The study suggests that freedom is not granted easily but is rather obtained by force. It also indicates that freedom is inherent in human nature and it is often enhanced by persistence, enriched by satisfaction, and prescribed by good legislations. The opinions obtained by the survey also suggest that there exists an utterly insignificant and limited space of freedom in Islamic societies. To yield fruitful results in our contemporary life, freedom must be originated from the servitude to the Almighty Allah by adhering to the Islamic constants in the Quran and Prophetic traditions and referring to Islamic legislation in which all rights are protected without favor nor exception.